The commercialization of the human body - Merkou (Μαρία Μέρκου) Maria (Bioethica, 2020)
The medical community has to confront the shortage of organs available for human transplantation, resulting in large waiting lists worldwide. Hence, the introduction of a donor reimbursement system, which would partly serve as an incentive is often proposed. This model leads us, however, to the much-disputed notion of the commercialization of the human body. This concept triggers a series of reactions of both moral and social interest. However, the philosophical justification of the actual legislative provisions is only used as a means to highlight the conflict between the various practices on the matter and is not itself the main focus of the present essay. In addition to solid organs, other parts of the body such as the human reproductive material and the bone marrow are used for both therapeutic and research purposes. Consequently, the following is an attempt to understand the concept of commercialization and whether it could act beneficially within certain contexts or contrariwise, cause great harm.